Dominant ecological paradigm expressed through the concept of sustainability in Spanish-speaking digital rheto-ric - Nalleli Salazar-Chapa; Gabriel Valerio-Ureña; Juan Milton Jair Aragón Palacios (Cuadernos.info, 2024)
The attitudes and behaviors of people toward nature have evolved throughout modern history. For a long time, the dominant paradigm was that of human beings as technocrats, leaders, and administrators of nature (anthropocentric paradigm). The discussion then begins about a new ecological paradigm, in which nature ceases to have only an instrumental value and obtains an intrinsic value (ecocentric paradigm). In recent years, scholars have postulated a reconciliation of both extremes with the creation of the concept of sustainable development. The objective of this qualitative research is to explore the extent to which this reconciliation is discernible in Spanish-speaking digital rhetoric by analyzing scientific articles, web pages, images, videos, and tweets. This study provides a starting point to monitor this type of controversy inside digital conversations and the importance of the topics, actors, and references related to this and other relevant trends. The results demonstrate that the dominant paradigm in digital content, that is, related to the theme of sustainability, is the ecocentric paradigm. The study concludes that this apparent reconciliation toward the ecocentric could be more of a product of a systematic greenwashing than that of a true sustainable practice.